The Validation of Korean Coaching Life Skills in Sport Questionnaire (KCLSS-Q) - Junsu Bae; Taehee Lim (Korea Institute of Sport Science, 2022)
PURPOSE The purpose of this study was to validate the Korean version of Coaching Life Skills in Sport Questionnaire (KCLSS-Q). METHODS Substantive, structural, and external stages were undertaken to address the purpose of this study. At the substantive stage, the scale was translated by discussing with an expert panel and testing item clarity. Ten coaches (9 males, Mage=33.80, SD=4.21) participated in the item clarity test. At the structural stage, descriptive statistics, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA) were conducted. A total of 249 (214 male, Mage=34.18, SD=6.82) and 232 coaches (186 male, Mage=34.26, SD=7.69) participated in the EFA and CFA, respectively. At the external stage, correlation analysis using other scales (emotional intelligence in sport coaching, EISSC) was conducted to examine concurrent validation. A total of 130 copies of the CFA data were randomly extracted and used for this stage. RESULTS For the EFA, the scale extracted five factors with 27 items. In the CFA, however, five factors with 26 items were identified as an appropriate structure. Finally, the relationships of all sub-factors between KCLSS-Q and EISSC were statistically significant in the correlation analysis. CONCLUSIONS KCLSS-Q should reasonably consists of nine items on structuring and facilitating a positive sport climate, five on understanding life skills, four on practicing life skills, five on understanding life skills transfer, and three on practicing life skills transfer. KCLSS-Q can be used as a valid measure to evaluate the coaching life skills of Korean coaches.